A Case of Multiple Carcinoid Tumors in the Ileum - Ueno, Masayoshi; Yoshida, Hideaki; Taki, Junichiro; Hokuto, Daisuke (Nippon Shokaki Geka Gakkai zasshi, 2005)
A 64-year-old man found in ultrasonography of the right lower abdomen to have a 4×3cm tumor was diagnosed with a tumor of the small intestine by computed tomography and small bowel radiography, necessitating surgery. The tumor was in fact found in the intestinal mesenterium, not in the small intestine, and 2 more tumors were found in the ileum. The ileum was partially resected and surgical specimens showed 3 tumors in the ileum (30×20mm, 3×3mm, 15×10mm), and a 50×50×30mm tumor in the mesenterium. Pathologically, the tumors in the ileum were carcinoid and that in the mesenterium was lymph node metastasis.